2008
DOI: 10.1017/s1368980007001061
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of the Andean population of Puna and Quebrada of Humahuaca, Jujuy, Argentina

Abstract: Objective: To assess the nutritional status of the Andean population of Puna and Quebrada of Humahuaca, Jujuy, using anthropometric measurements. Design and subjects: A cross-sectional nutritional survey was carried out in a representative sample (n 5 1236) of individuals from these regions. Children aged 2-9 years, adolescents (10-17 years) and adults ($18 years; pregnant and lactating women excluded) were considered. Height-for-age, weight-for-height and body mass index (BMI) were calculated in children and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
2
16
0
2
Order By: Relevance
“…1 Weight-for-age and height-for-age P50 of Tibetan children and WHO growth curves [17] and −1.34 (1.52), respectively. Stunting was present in nearly half of the children (Table 1) and severe stunting in 26% of them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Weight-for-age and height-for-age P50 of Tibetan children and WHO growth curves [17] and −1.34 (1.52), respectively. Stunting was present in nearly half of the children (Table 1) and severe stunting in 26% of them.…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with previous observations from Tibet [4,8,9] and from comparable environments in the Himalaya [5], as well as in other parts of the world. Stunting is observed, for instance, in 10.7% of children living at high altitude, both in rural and urban environments, in the Andes [17]. This does not imply, however, that altitude is the cause of growth retardation.…”
Section: Discussionmentioning
confidence: 98%
“…Within this context, a great percentage of individuals who experienced chronically poor nutrition in their early lives, and are thus stunted, seem to be more predisposed to obesity later in life (Florencio et al, 2003(Florencio et al, , 2007Martins et al, 2004;Grillo et al, 2005;Romaguera et al, 2008;Said-Mohamed et al, 2009;Ferreira et al, 2009;Sichieri et al, 2010;Alves et al, 2011). Individuals with chronic under-nutrition (stunting) in early life seem to have reduced energetic demands through metabolic (Soares-Wynter and Walker, 1996;Frisancho, 2003;Grillo et al, 2005;Said-Mohamed et al, 2009 and behavioral shifts (Spurr and Reina, 1988;Hoffman et al, 2000;Wilson et al, 2012).…”
mentioning
confidence: 99%
“…In particular, WAZ and BMIZ comparisons showed that ecological differences between peri-urban and rural groups resulted in a gradient where the former showed some of the telltale signs of the transition to a Westernized life style. Unlike non-Native Argentines, the Qom show a positive association between socioeconomic status and BMI (Valeggia et al, 2010), which has been observed in other Argentinean indigenous groups (Orden and Oyhenart, 2006;Romaguera et al, 2008) for whom heavy individuals are regarded as "healthy" (Valeggia et al, 2010). Among non-Native Argentine, increased levels of urbanization likely accompanied by dietary changes and low activity levels lead to significantly higher frequencies of obese and overweight individuals (Dahinten et al, 2011;Hirschler et al, 2008;Kovalskys et al, 2011;Ramirez-Zea et al, 2014).…”
Section: Discussionmentioning
confidence: 89%
“…Among non-Native Argentine, increased levels of urbanization likely accompanied by dietary changes and low activity levels lead to significantly higher frequencies of obese and overweight individuals (Dahinten et al, 2011;Hirschler et al, 2008;Kovalskys et al, 2011;Ramirez-Zea et al, 2014). Unlike non-Native Argentines, the Qom show a positive association between socioeconomic status and BMI (Valeggia et al, 2010), which has been observed in other Argentinean indigenous groups (Orden and Oyhenart, 2006;Romaguera et al, 2008) for whom heavy individuals are regarded as "healthy" (Valeggia et al, 2010). Moreover, a previous study has shown that Westernized Qom adults show a prevalence of obesity that is above 45% (Lagranja et al, 2015).…”
Section: Discussionmentioning
confidence: 92%